2011
DOI: 10.1007/s10397-011-0683-7
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted radical hysterectomy—perioperative and survival outcomes in patients with cervical cancer compared to laparoscopic and open radical surgery

Abstract: In this study, perioperative outcomes and survival data in patients with early cervical cancer operated with three surgical methods: robot-assisted, laparoscopic and open, are to be analyzed. From January 2006 to May 2010, 294 patients with T1в1 cervical cancer were studied retrospectively. Robot-assisted radical hysterectomy (RARH) was performed in 73 (24.8%) of them, laparoscopic-assisted radical vaginal hysterectomy (LARVH) in 46 (15.6%) and, in 175, (59.5%), abdominal radical hysterectomy (ARH). Mean hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 21 publications
1
24
1
1
Order By: Relevance
“…All included studies were retrospective cohort design. Ten studies were conducted in the United States of America (USA) [10,11,16,17,21,22,24,33,36,47], 4 studies in Korea [13,20,25,37], 3 studies in Italy [14,23,46], 2 studies in Norway [31,32], 1 study in Sweden [29], 1 study in France [15], 1 study in Bulgaria [18], 1 study in Canada [19], 1 study in Czech [28], 1 study in Taiwan [12] and 1 study in both USA and Italy [34]. Overall, the studies had adequate methodological quality and low risk of bias, particularly in terms of cohort selection and outcome ascertainment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All included studies were retrospective cohort design. Ten studies were conducted in the United States of America (USA) [10,11,16,17,21,22,24,33,36,47], 4 studies in Korea [13,20,25,37], 3 studies in Italy [14,23,46], 2 studies in Norway [31,32], 1 study in Sweden [29], 1 study in France [15], 1 study in Bulgaria [18], 1 study in Canada [19], 1 study in Czech [28], 1 study in Taiwan [12] and 1 study in both USA and Italy [34]. Overall, the studies had adequate methodological quality and low risk of bias, particularly in terms of cohort selection and outcome ascertainment.…”
Section: Resultsmentioning
confidence: 99%
“…We excluded 3 studies that evaluated different procedures or disease stages [43][44][45], 1 that included some cases of radical trachelectomy in the treatment cohort [9], 1 which was a protocol for a randomized controlled trial (RCT) [27], and 1 commentary [26]. Overall, 26 comparative studies that met the inclusion criteria were available for pooled analysis [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]28,29,[31][32][33][34]36,37,46,47]. Only 1 study included a mixed cohort of cervical and endometrial cancer cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all 11 published studies comparing RRH with TLRH for the treatment of cervical cancer, the largest study included only 73 patients that underwent RRH surgery compared with 46 patients that opted for a TLRH procedure. 27 Although many of those studies include only stages IA and IB cervical cancer patients, we have also enrolled patients with stage IIA in our study. Similar to previously published studies, most of the patients had a squamous cell carcinoma but other tumor types were also identified in both groups including adenocarcinoma, neuroendocrine carcinoma, and adenosquamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews of observational studies have shown that a minimal access approach with either standard laparoscopy or robotics was associated with a shorter hospital stay, less complications, less blood loss, and lower transfusion rates [ 6 7 8 ]. This is in the background of recurrence rates being reported as similar in both minimally invasive and open arms [ 9 10 11 12 13 ].…”
mentioning
confidence: 82%